2020
DOI: 10.1158/1535-7163.mct-19-0437
|View full text |Cite
|
Sign up to set email alerts
|

The Existence of MTH1-independent 8-oxodGTPase Activity in Cancer Cells as a Compensatory Mechanism against On-target Effects of MTH1 Inhibitors

Abstract: Investigations into the human 8-oxodGTPase, MutT Homolog 1 (MTH1), have risen sharply since the first-in-class MTH1 inhibitors were reported to be highly tumoricidal. However, MTH1 as a cancer therapeutic target is currently controversial because subsequently developed inhibitors did not exhibit similar cytotoxic effects. Here, we provide the first direct evidence for MTH1-independent 8-oxodGTPase function in human cancer cells and human tumors, using a novel ATP-releasing guanine-oxidized (ARGO) chemical prob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…We have previously shown that MTH1 expression and 8-oxo-dGTPase activity are elevated in human lung adenocarcinomas relative to counterpart normal tissues [ 4 , 19 , 37 , 38 ]. To assess whether OGG1/MTH1 co-inhibition is likely to enhance anti-tumor outcomes, we evaluated whether OGG1 levels were elevated globally in human lung adenocarcinoma specimens or in tumor subsets without enhanced MTH1 expression.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that MTH1 expression and 8-oxo-dGTPase activity are elevated in human lung adenocarcinomas relative to counterpart normal tissues [ 4 , 19 , 37 , 38 ]. To assess whether OGG1/MTH1 co-inhibition is likely to enhance anti-tumor outcomes, we evaluated whether OGG1 levels were elevated globally in human lung adenocarcinoma specimens or in tumor subsets without enhanced MTH1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate the molecular effects of MTH1/OGG1 co-inhibition, we treated A549 cells with a novel small molecule OGG1/MTH1 co-inhibitor SU0383 31 as well as with SU0268, IACS-4759 (a second-generation MTH1 inhibitor with minimal off-target effects [ 15 , 19 ]) or with a combination of SU0268/IACS-4759, the two molecules which make up the SU0383 scaffold ( Fig. 5 A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, this process has focused interest on using inhibition of 8-oxodGTPases as a therapeutic target in cancer [ 62 ] as, due to their faster rate of proliferation, and increased intracellular ROS, cancer cells are thought to have greater reliance on enzymes, such as the 8-oxodGTPases [ [63] , [64] , [65] ]. However, the results from the various studies exploring this area have been mixed between positive [ [66] , [67] , [68] ] and negative [ 69 , 70 ], although this may arise from differences in the inhibitors, the experimental systems being used [ 71 ], and redundancy in the pathways being inhibited [ 72 ].…”
Section: Formation Repair and Consequences Of Damage To Nucleic Acidsmentioning
confidence: 99%